The potential causative factors in discitis after lumbar macrodiscectomy - (:unkn) unknown (My University, 2003)
Objective: Development of discitis after lumbar discectomy is one of the most important complications of disc surgery. This retrospective study investigated the influence of potential contributing factors in 9 cases of postoperative discitis occurring in 2901 patients who underwent macrodiscectomy. Methods: The specific factors considered were age, sex, history of diabetes mellitus, level of the herniated disc, number of levels operated, occurrence of dural tear and cerebrospinal fluid fistula during surgery, postoperative superficial wound infection, and antibiotic regime. Concerning the latter, Group 1 (n=471) received triple-drug multi-dose antibiotic prophylaxis, and Group 2 (n=2430) received single-drug single-dose antibiotic prophylaxis. Results: The overall incidence of postoperative discitis in the series was 0.31%. Five of the discitis patients were in Group 1 and four were in Group 2, thus the group rates of postoperative discitis were 1.06% and 0.16%, respectively. The frequencies of discitis according to level of disc herniation were 0.91% for L3-L4, 0.36% for L4-L5, and 0.33% for L5-S1. There was no correlation between postoperative discitis and post-surgery superficial wound infection. Conclusion: The study showed that administering a single prophylactic dose of one antibiotic prior to surgery reduces the risk of postoperative lumbar discitis and superficial wound infection. Of the factors investigated, antibiotic regimen was the only one that was significantly associated with postoperative discitis.
Keywords: Discectomy; Discitis; Lumbar disc herniation